Seropositivity of measles antibodies in the Israeli population prior to the nationwide 2018 – 2019 outbreak. Issue 5 (4th May 2021) - Bassal, Ravit; Indenbaum, Victoria; Pando, Rakefet; Levin, Tal; Shinar, Eilat; Amichay, Doron; Barak, Mira; Ben-Dor, Anat; Haim, Adina Bar; Mendelson, Ella; Cohen, Dani; Shohat, Tamy
ABSTRACT: Measles vaccine is administered in Israel as part of the routine childhood immunization program, at ages 1 and 6 years. In this study, we assessed seropositivity of the Israeli population against measles before the onset and propagation of the 2018–2019 measles outbreak. From the Israel Center for Disease Control National Serum Bank, 3, 164 samples collected during 2015 were tested for measles antibodies. All the tests were performed using Enzyme-Linked Immunosorbent Assay (ELISA) commercial kit (Enzygnost, Anti-Measles Virus/IgG: Behring, Marburg, Germany). The overall seropositivity rate for measles was 90.7%. The seropositivity rate at 6 months and younger was 48.9%, and decreased to 3.8% among infants aged 6–11 months. Seropositivity increased to 90.7% in the 1-4-year age group, and reached 96.1% for 5–9 year-old children. Our results suggest high immunity in the Israeli population against measles virus, but not high enough to prevent outbreaks because of pockets of specific population groups with low immunization coverage. Infants between ages 6 and 11 months and children younger than 2 years had the lowest seropositivity rates being the age groups with the highest attack rates of measles during the epidemic of 2018. Efforts should be aimed at avoiding any delay in vaccination once a child reaches the age of 1 year and improving immunity levels in children aged 1–4 years.